1997
DOI: 10.1002/eji.1830270812
|View full text |Cite
|
Sign up to set email alerts
|

The selective engulfment of apoptotic bodies by dendritic cells is mediated by the αvβ3 integrin and requires intracellular and extracellular calcium

Abstract: Dendritic cells derived in vitro from monocytes are known to be poor phagocytes. Here we show that, unlike macrophages, monocyte-derived dendritic cells indeed fail to take up opsonized particles or necrotic cells; however, apoptotic bodies are efficiently engulfed by dendritic cells. The temperature dependence and the sensitivity to cytochalasin D indicate that the apoptotic body engulfment is representative of early stages of phagocytosis. Inhibition studies with ligands for surface molecules involved in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
2
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(155 citation statements)
references
References 38 publications
4
144
2
5
Order By: Relevance
“…Sub-G 1 DNA content, assayed by staining with PI Necrotic cells were produced by two methods that have been used by others for this purpose: treatment with heat (Rubartelli et al, 1997) or the mild detergent digitonin (Single et al, 1998). They were also produced by freeze -thawing.…”
Section: Resultsmentioning
confidence: 99%
“…Sub-G 1 DNA content, assayed by staining with PI Necrotic cells were produced by two methods that have been used by others for this purpose: treatment with heat (Rubartelli et al, 1997) or the mild detergent digitonin (Single et al, 1998). They were also produced by freeze -thawing.…”
Section: Resultsmentioning
confidence: 99%
“…Future work should take into account the possibility that clearance mechanisms dedicated to removal of late apoptotic cells could exist. Some support for this possibility can be drawn from the observation by Rubartelli et al that myeloid dendritic cells may use ␣ v integrins in selective ingestion of late apoptotic cells (26).…”
Section: Figurementioning
confidence: 99%
“…A number of different types of phagocytes can deploy the phagocyte surface ␣ v ␤ 3 vitronectin receptor integrin to present bridging thrombospondin 1 (TSP1) to apoptotic cells and promote phagocytosis without inciting proinflammatory secretory responses (10,11,23,24). This mechanism was a strong candidate for M recognition of late apoptotic neutrophils, because 1) these cells exhibit limited fusion with the plasma membrane of granules containing proteins capable of binding TSP1 (21,22,25); 2) a very recent report indicates that late apoptotic neutrophils bind TSP1 with such efficiency that this can be demonstrated with soluble biotinylated TSP1 (19); and 3) myeloid dendritic cells bind late apoptotic cells via an ␣ v -mediated mechanism (26). However, equally strong candidate phagocyte receptors were those of the ␤ 2 integrin family that bind opsonic complement fragments, type 3 complement receptor (CR3; ␣ m ␤ 2 or CD11b/CD18) and CR4 (␣ x ␤ 2 or CD11c/ CD18).…”
mentioning
confidence: 99%
“…Albert et al reported that immature DC are capable of phagocytosis of apoptotic cells, although not as efficiently as macrophages [25,44] and that they can cross-present viral, tumor, and selfantigens to CD8+ T cells [45]. Moreover, it was recently suggested that apoptotic cells are able to promote maturation of DCs by upregulating costimulatory molecules and inducing proinflammatory cytokine release, while functioning as endogenous adjuvants for the induction of specific T cell responses [46].…”
Section: The Adaptive Immune Response To Apoptotic Cells Antigen Presmentioning
confidence: 99%